KEMAMPUAN MATEMATIS MAHASISWA PGSD PADA MATA KULIAH RME MATERI JENIS BILANGAN - Astuti Astuti; Syahfitriani Br Ginting; Dessy Rizki Suryani; Serlina Boru Sinaga (Program Studi PGSD Universitas Flores, 2023)
Mathematical abilities need to be possessed on the grounds of being able to equip life in solving problems regularly. The RME course bridges students to study mathematics in everyday life. The research was conducted to determine the mathematical thinking abilities of PGSD students in the RME course on number types. The type of research carried out was descriptive qualitative with the use of random sampling to determine 3 research subjects (high, medium and low mathematical abilities). The stages that were passed were the lecturer making questions, assessment criteria, conducting tests, scoring and assessment ending with data reduction assisted by MS Excel. The data obtained was that there were 16.67% students in the high mathematical ability category, 75% in the medium category and 8.33% in low mathematical ability. MS excel calculations show that the average value of students' mathematical ability is 52.78, so it is in the medium category. Students with high mathematical abilities are very good at understanding the material on odd numbers as well as irrational numbers, both on prime numbers and need guidance on prime numbers. Understanding of prime numbers is very good, good for even numbers as well as odd numbers but needs improvement in irrational numbers for students with moderate mathematical abilities. Students with low mathematical abilities have a good understanding of prime numbers, understand enough material for odd and even numbers and have no clue about irrational numbers.